Community perceptions and practices of treatment seeking for childhood pneumonia: a mixed methods study in a rural district, Ghana - Mercy Abbey; Margaret A. Chinbuah; Margaret Gyapong; L. Kay Bartholomew; Bart van den Borne (BMC, 2016)
Abstract Background The World Health Organization recommends community case management of malaria and pneumonia for reduction of under-five mortality in developing countries. Caregivers' perception and understanding of the illness influences the care a sick child receives. Studies in Ghana and elsewhere have routinely shown adequate recognition of malaria by caregivers. Similarly, evidence from Asia and some African countries have shown adequate knowledge on pneumonia. However, in Ghana, little has been documented about community awareness, knowledge, perceptions and management of childhood pneumonia particularly in the Dangme West district. Therefore this formative study was conducted to determine community perceptions of pneumonia for the purpose of informing the design and implementation of context specific health communication strategies to promote early and appropriate care seeking behaviour for childhood pneumonia. Methods A mixed method approach was adopted. Data were obtained from structured interviews (N = 501) and eight focus group discussions made up of 56 caregivers of under-fives and eight community Key Informants. Descriptive and inference statistics were used for the quantitative data and grounded theory to guide the analysis of the qualitative data. Results Two-thirds of the respondents had never heard the name pneumonia. Most respondents did not know about the signs and symptoms of pneumonia. For the few who have heard about pneumonia, causes were largely attributed to coming into contact with cold temperature in various forms. Management practices mostly were self-treatment with home remedies and allopathic care. Conclusion The low awareness and inadequate recognition of pneumonia implies that affected children may not receive prompt and appropriate treatment as their caregivers may misdiagnose the illness. Adequate measures need to be taken to create the needed awareness to improve care seeking behaviour.